Application of 2D-GCMS reveals many industrial chemicals in airborne particulate matter - Alam, M.; West, C.; Scarlett, Alan; Rowland, S.; Harrison, R. (2013)
Samples of airborne particulate matter (PM2.5) have been collected in Birmingham, UK and extracted with dichloromethane prior to analysis by two-dimensional GC separation and TOFMS analysis. Identification of compounds using the NIST spectral library has revealed a remarkable diversity of compounds, some of which have not been previously reported in airborne analyses. Groups of compounds identified in this study include a large number of oxygenated VOC including linear and branched compounds, substituted aromatic compounds and alicyclic compounds, oxygenated polycyclic aromatic and alicyclic compounds, organic nitrogen compounds, branched chain VOC and substituted aromatic VOC, phthalates, organo-phosphates and organo-sulphate compounds. Many of the compounds identified are mass production chemicals, which due to their semi-volatility enter the atmosphere and subsequently partition onto pre-existing aerosol. Their contribution to the toxicity of airborne particulate matter is currently unknown but might be significant. The diverse industrial uses and potential sources of the identified compounds are reported. © 2012 Elsevier Ltd.